Using Google Meet breakout rooms for group work / Aileen Farida Mohd Adam and Mohd. Suhaimi Sulaiman - Mohd Adam, Aileen Farida; Sulaiman, Mohd. Suhaimi (Academy of Language Studies, 2021)
Open Distance Learning (ODL) has been implemented in UiTM since April 2020 due to the COVID-19 pandemic and it comes with its own set of challenges. For example, some of the students’ biggest challenges in their online learning were due to the lack of time management skills, poor Inter-net connection and noisy home environment (Aileen Farida Mohd Adam et al., 2021). Meanwhile, from lecturers' own limited experiences teaching online, one of the biggest challenges is carrying out group work